A nationwide birth year‐by‐year analysis of effectiveness of HPV vaccine in Japan. Issue 9 (22nd July 2021) - Yagi, Asami; Ueda, Yutaka; Nakagawa, Satoshi; Masuda, Tatsuo; Miyatake, Takashi; Ikeda, Sayaka; Abe, Hazuki; Hirai, Kei; Sekine, Masayuki; Miyagi, Etsuko; Enomoto, Takayuki; Nakayama, Tomio; et al.
Abstract: In Japan, the age‐adjusted incidence of cervical cancer has been increasing constantly and rapidly among younger women. We set out to accurately confirm the effectiveness of the HPV vaccine in Japan. Data were collected for women born in the fiscal year (FY) 1990 to 1997, who became eligible for their 20‐y‐old cervical cancer screening between the FY 2010 to 2017. The adjusted incidence of cervical intraepithelial neoplasia (CIN)1+ in women born in FY 1990 to 1993, that is those who reached the national vaccination target age prior to the introduction of publicly subsidized HPV vaccinations, referred here after as "the pre‐introduction generation", was 1.42% (242/17 040). The incidence in the "vaccination generation" (women born in FY 1994 to 1997, that is those who were heavily vaccinated as a group when they were of the nationally targeted age of 13‐16) was 1.66% (135/8020). There was no significant difference between these incidence rates. However, our FY birth year‐by‐year analysis revealed that the incidence of CIN1+ was obviously lower than that predicted based on just the trend for CIN1+ seen in the pre‐introduction generation. Our analysis revealed that the incidence of CIN3+ was obviously lower in the vaccination generation than in the pre‐introduction generation ( P  = .0008). The incidence of CIN was already tending to increase in both the pre‐introduction and vaccination generations. The changes in CIN incidence by individual birth FY must be examined to accurately determine the actual effects of the HPV vaccine for reducing mild cervical lesions. Abstract : This is the first large‐scale study in Japan to show a significant preventive effect of HPV vaccine against CIN3+. The incidence of CIN1+ was the same in both the vaccination and the pre‐introduction generation. Because the incidence of CIN 1+ was tending to increase in both generations, the changes in CIN 1+ incidence by individual birth FY must be examined to accurately determine the actual effects of HPV vaccine for reducing mild cervical lesions.